CONSIDERACIONES SOBRE EL ESPLENDOR DE AYER: ARQUITECTURA Y POESÍA EN CARLOS DRUMMOND DE ANDRADE. - Roig, Maribel (Revista de Critica Literaria Latinoamericana, 2003)
The article presents a literary analysis of the work of 20th century Brazilian poet Carlos Drummond de Andrade, focusing specifically on the representations of architecture in Drummond's work. The poem "Edificio Esplendor" is analyzed in depth, in addition to "A um Hotel em Demolição" and "Avenida." The author concludes with a discussion of the construction of a nationalist Brazilian architecture through Drummond's words.